Iatrogenic withdrawal syndrome in adult intensive care unit: a scoping review - Moisa, Emanuel; Tuculeanu, Georgeana; Corneci, Dan; Negoita, Silvius Ioan; Bilotta, Federico (Frontiers in Medicine, 2025)
IntroductionFollowing prolonged opioid and/or hypnotic exposure, iatrogenic withdrawal syndrome (IWS) can develop in critically ill patients due to improper cessation of these drugs. While IWS is well-documented in pediatric and neonatal intensive care unit (ICU), research on adult ICU patients remains scarce. This scoping review aimed to map existing evidence on IWS in critically ill adults, focusing on diagnosis, epidemiology, risk factors, complications, clinical effects, treatment, and prevention.MethodsA literature search across PubMed, Scopus, and Web of Science included studies from 1990 to 2024 with prospective, retrospective, or randomized controlled trial designs. Out of 3105 retrieved titles, 29 studies met inclusion criteria.ResultsMost studies addressed diagnosis (83%) and epidemiology (79%), with IWS definitions largely adapted from chronic drug users. Incidence varied from 13.6 to 49.5%. Several studies identified risk factors, primarily therapy-related, but only some performed robust statistical analyses. Complications and clinical effects were discussed in 12 studies but results on ICU and hospital outcomes were inconsistent. Physiological studies linked IWS to sympathetic overactivity and central nervous system excitability. Only 20% of studies examined treatment or prevention, with randomized trials assessing substitution therapy. Most strategies did not significantly alter IWS incidence, though clonidine showed potential benefits.DiscussionThis review highlights critical knowledge gaps and the lack of consensus or guidelines for IWS in adult ICU patients, emphasizing the need for further research.